Current evidence for designing self-management support for underserved populations: an integrative review using the example of diabetes - Ian Litchfield; Tim Barrett; Julian Hamilton-Shield; Theresa Moore; Parth Narendran; Sabi Redwood; Aidan Searle; Suma Uday; Jess Wheeler; Sheila Greenfield (BMC, 2023)
Abstract Aims With numerous and continuing attempts at adapting diabetes self-management support programmes to better account for underserved populations, its important that the lessons being learned are understood and shared. The work we present here reviews the latest evidence and best practice in designing and embedding culturally and socially sensitive, self-management support programmes. Methods We explored the literature with regard to four key design considerations of diabetes self-management support programmes: Composition - the design and content of written materials and digital tools and interfaces; Structure - the combination of individual and group sessions, their frequency, and the overall duration of programmes; Facilitators - the combination of individuals used to deliver the programme; and Context - the influence and mitigation of a range of individual, socio-cultural, and environmental factors. Results We found useful and recent examples of design innovation within a variety of countries and models of health care delivery including Brazil, Mexico, Netherlands, Spain, United Kingdom, and United States of America. Within Composition we confirmed the importance of retaining best practice in creating readily understood written information and intuitive digital interfaces; Structure the need to offer group, individual, and remote learning options in programmes of flexible duration and frequency; Facilitators where the benefits of using culturally concordant peers and community-based providers were described; and finally in Context the need to integrate self-management support programmes within existing health systems, and tailor their various constituent elements according to the language, resources, and beliefs of individuals and their communities. Conclusions A number of design principles across the four design considerations were identified that together offer a promising means of creating the next generation of self-management support programme more readily accessible for underserved communities. Ultimately, we recommend that the precise configuration should be co-produced by all relevant service and patient stakeholders and its delivery embedded in local health systems.